Traumatic cardiac arrest is associated with lower survival rate vs. medical cardiac arrest – Results from the French national registry. (October 2018) - Escutnaire, Joséphine; Genin, Michael; Babykina, Evgéniya; Dumont, Cyrielle; Javaudin, François; Baert, Valentine; Mols, Pierre; Gräsner, Jan-Thorsten; Wiel, Eric; Gueugniaud, Pierre-Yves; Tazarourte, Karim; Hubert, Hervé; et al.
Abstract: Introduction: The survival from traumatic vs . medical out-of-hospital cardiac arrest (OHCA) are not yet well described. The objective of this study was to compare survival to hospital discharge and 30-day survival of non-matched and matched traumatic and medical OHCA cohorts. Material & methods: National case-control, multicentre study based on the French national cardiac arrest registry. Following descriptive analysis, we compared survival rates of traumatic and medical cardiac arrest patients after propensity score matching. Results: Compared with medical OHCA ( n  = 40, 878) trauma victims ( n  = 3209) were younger, more likely to be male and away from home at the time and less likely to be resuscitated. At hospital admission and at 30 days their survival odds were lower (OR: respectively 0.456 [0.353;0.558] and 0.240 [0.186;0.329]). After adjustment the survival odds for traumatic OHCA were 2.4 times lower at admission (OR: 0.416 [0.359;0.482]) and 6 times lower at day 30 (OR: 0.168 [0.117;0.241]). Conclusions: The survival rates for traumatic OHCA were lower than for medical OHCA, with wider difference in matched vs . non-matched cohorts. Although the probability of survival is lower for trauma victims, the efforts are not futile and pre-hospital resuscitation efforts seem worthwhile.